Experimentos de pulverização de batata americana - Kremer Luz, Ney (Revista Ceres, 2024)
In six P. infestans control experiments with potatoes a high protection against the disease and a very good yield increase were conferred by the following fungicides: Cuprosan, Perenox, Copper Compound A, Bordeaux mixture, Cupravit Ob 21, Dithane Z-78 and Dithane M-22. Satisfactory results were also obtained by Manzate, Blue Cuprosan, Polyram (polyethylene tiuram disulphide) and Vitigram Conc. Fermate, Parzate, Rhodiazinc E-50 (ziram) and Blemco Estanho (stannic triphenylacetate) gave no effective results. The yield increase varied according to the year, reaching more than 100% over the check and with five applications. The number of sprays ranged from two to five. It was observed a remarkable correspondence between disease control and yield. A less distinct correspondence were noted between yield and percentage of marketable tubers (weight above 20 g). Blemco Estanho, and in less degree Bordeaux misture, have shown phytotoxicity on the potato plant.